Formation of ZIF-8 membranes and crystals in a diluted aqueous solution - Yao, J.; Li, L.; Wong, W.H.; Tan, C.; Dong, Dehua; Wang, H. (Elsevier Science SA, 2013)
Alumina hollow fiber supported ZIF-8 membranes and crystals have been prepared in diluted aqueoussolutions. The concentration of the aqueous solution, synthesis temperature and time were examined in detail. The particle sizes of ZIF-8 crystals increased from about 90 nm to 5.0 micrometers with the increase of the dilution of the aqueous synthesis solution. Continuous ZIF-8 membranes were obtained by using the diluted synthesis solution with a Zn2+:2-methylimidazolate:H2O molar ratio of 1:70:4952 at 50-70 degrees Celcius for 24 h, and their thicknesses were about 0.8-1.4 mm. Gas permeation tests indicated the ZIF-8 membranes are continuous and compact. The schematic formation of ZIF-8 membranes and crystals were proposed, and only in the diluted aqueous solution, ZIF-8 membranes and crystals could be prepared at the same time.